Estudo comparativo dos níveis de expectativa e de satisfação com a interiorização do Instituto Federal do Ceará nos campi dos municípios de Aracati, Canindé e Sobral na perspectiva dos discentes. - Fonseca, Heloisa Helena Medeiros da (2018)
In Brazil, the access to higher education was the privilege of a few. The National Education Plan (PNE) 2001-2010, and the PNE 2011-2020, have in their guidelines the indication that a strong system of higher education is the main factor for the development and independence of a country. These plans established a policy of expansion to reduce inequalities of offer without renouncing quality in education. The Law 11,892 of December 29, 2008, which create the Federal Institutes (FI) establishes one of the expansion policies in order to meet the demand for higher education in the capitals and in the country interior. This study is classified as an applied research, with a quantitative approach and for exploratory and descriptive purposes, its general objective is to investigate the degree of expectation and satisfaction with the effects that the expansion policy promoted with the interiorization of the IFCE in the campuses of the cities of Aracati, Canindé and Sobral in the perspective of the students. The choice of campuses was based on the criterion: date of creation, courses offered and the situation of the city in relation to higher education. The research universe is represented by the 1,677 students enrolled in undergraduate courses of the analyzed campuses and the sample size was calculated in 301 students. The data collection tool uses a questionnaire adapted from the model of Schleich, Polydoro and Santos (2006), structured in four dimensions: the academic, the institutional, the expansion policy and the perspective of future where will be measured the expectation and satisfaction of the undergraduate students of the campuses of Aracati, Canindé and Sobral. In the analysis of the results was applied exploratory data analysis and statistical inference, through the test of non-parametric hypotheses (Wilcoxon and Kruskal-Wallis). The results show that the degree of expectation of respondents in all dimensions is greater than that of satisfaction, however, in the global average satisfaction reached a satisfactory degree. The survey also revealed a difference of results among campuses, where the Canindé campus had the highest expectation index and the Sobral campus had the highest satisfaction rate. The Expansion Dimension presented the lowest satisfaction means, however, the first item of this dimension: as for the creation of the campus in its city, the satisfaction obtained a higher average than the expectation in the three campuses. This study concludes that the policy of expansion of higher education, although did not meet the expectations, obtained a satisfactory degree in the attribute of the student's satisfaction with regard to access to higher education in the region where he resides.